Kebiasaan Makan Ikan Tilan (Mastacembelus erythrotaenia) di Sungai Landak Desa Kuala Mandor A, Kabupaten kbu Raya - Atmaja, Yulius Yudhie Darma; Kurniadi, Bambang (Akuatik Tropis: Journal of Tropical Aquatic Resource Management, 2024)
ABSTRACTFish feeding habits are the amount and quality of food that fish eat. Food habits are one aspect that affects the growth and survival of fish. This study aims to understand and study the eating habits of tilan fish in the Landak River Kuala Mandor A, Kubu Raya Regency by analyzing data such as relative intestinal length, stomach fullness index and the composition of food types and determine the condition of the water environment. in the Porcupine river. The research was conducted for 5 months, that is in desember 2022 "“ april 2023 at four different stations using the Purposive Sampling method. Fish samples were grouped based on station and length. Analysis of food habits using the quantitative (qualitative) method by counting the amount and type of food found in the intestine and stomach of tilan fish. The results of the study obtained from 30 samples of tilan fish showing relative intestinal length (RLG) of tilan fish show that tilan fish is a carnivorous fish with RLG value in the range of 0.32 - 0.42 or less than 1. The main food is. crab (Sesarma eydouxi), supplementary food is phytoplankton, zooplankton and worms, supplementary food is dominated by detritus. Water quality in Kali Landak, water temperature between 29.08 °C - 29.83 °C. The brightness parameter value ranges from 40.33 cm - 45.83 cm. The resulting pH parameters are 5.57 - 5.69. The DO value is between 3.96 - 4.81 mg/l. The current speed parameter value is 0.31 - 0.33 cm/sec. As for the water parameters in the depth between 4.00 - 5.16 meters.